165k views
4 votes
Can someone step by step explain this to me?

Which is a simplified form of the expression -4(3r – 2) – 2(r + 1)?
Whoever helps gets 50 bonus points.

2 Answers

4 votes

-4(3r - 2) - 2(r + 1) = 0

-12r + 8 - 2r - 2 = 0

-14r + 6 = 0

-14r = - 6

r = 6/14

r = 3/7

5 votes

Answer:


\huge\boxed{\sf -14r+6}

Explanation:


\sf -4(3r-2)-2(r+1)\\\\Resolving \ Parenthesis\\\\= -12r+8-2r-2\\\\Combining \ like \ terms\\\\= -12r -2r +8-2\\\\= -14r+6\\\\\rule[225]{225}{2}

Hope this helped!

~AH1807

User Rby
by
6.4k points